The level of Emotional stability among a sample of theoretical college students (A field study at Tishreen University) - تركماني, مي; فؤاد صبيره , (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aims to identify the level of emotional stability among a sample of theoretical college students. The sample consisted of (400) male and female students from Tishreen University students in Lattakia Governorate. The scale which used in this research is emotional stability, according to the curriculum descriptive. Researcher used statistical methods as following: (T test, Alfa test). The research found that: More than half of the respondents had emotional stability at an average level (61%). There is a difference between the mean of the respondents’ mean responses on the emotional stability scales attributable to gender variable in favor of females, attributable to the year of study in favor to the last year, but no differences attributable to the educational level of father. In view of the results of the research, a number of proposals were presented, the most important of which are: attention to psychological preparation for students, the use of psychological tests as an objective way to evaluate the status of students, and the preparation of counseling programs related to the problems they are experiencing psychologically during the university stage. Key words: Emotional stability